The Impact of Supplementation and Adjuvant Pharmacotherapy on Bone Fracture Healing - Machnio, Bartosz; Świątek, Agata; Andruszkiewicz, Kamil; Jasińska, Natalia; Frączyk, Wojciech; Krysiak, Mateusz; Błachowska, Bogna; Turzyńska, Natalia; Mania, Katarzyna; Bąk, Julia (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Bone fractures and healing complications, such as delayed union and non-union, present a substantial and growing global healthcare burden. While surgical fixation techniques have advanced significantly, optimizing the biological environment through targeted nutritional and pharmacological interventions remains critical for successful osteogenesis. This review aims to systematize the current knowledge regarding the impact of exogenous supplementation and adjuvant pharmacotherapy - ranging from basic nutrients to advanced biological drugs - on the bone fracture healing process. A brief description of the state of knowledge: Based on a comprehensive literature search of major medical databases focusing on the last 15 years, the synthesis of clinical and preclinical data indicates that correcting baseline nutritional deficiencies (particularly protein, amino acids, and vitamin D3) is an essential prerequisite for adequate soft callus formation and subsequent mineralization. Structural components like chondroitin sulphate and collagen, alongside phytotherapeutics such as Cissus quadrangularis, provide significant early-stage support for endochondral ossification. Conversely, routine administration of non-steroidal anti-inflammatory drugs (NSAIDs) during the acute inflammatory phase should be approached with high caution due to their potential to significantly delay healing. In recalcitrant cases, advanced therapies like systemic teriparatide and locally applied bone morphogenetic proteins (BMPs) offer potent osteoinductive rescue strategies. Summary (conclusions): A multifaceted approach that integrates early nutritional optimization, judicious analgesic management, and targeted osteoinductive pharmacotherapy is vital for enhancing physiological bone repair, reducing recovery time, and preventing severe non-union complications.